Growth and characterization of W thin films with controlled Ne and Ar contents deposited by bipolar HiPIMS. (December 2021) - Tiron, V.; Bulai, G.; Costin, C.; Velicu, I.-L.; Dincă, P.; Iancu, D.; Burducea, I.
Highlights: Successful growth of W films with Ne-Ar contents up to 3 at.% using bipolar HiPIMS. The amount of Ne-Ar in W films is determined by ion energy and flux to substrate. Ion energy is related to positive pulse voltage, ion flux to negative pulse width. Highest film crystallinity for a positive pulse of 200 V and a negative pulse of 5 µs. Abstract: This work is focused on controlling and optimizing the inclusion of neon (Ne) and argon (Ar) impurities in tungsten (W) reference coatings. A tungsten target has been sputtered in monopolar and bipolar High Power Impulse Magnetron Sputtering (HiPIMS) operation modes, in Ar-Ne gas mixture. It has been found that the process of noble gas retention in W thin layers is strongly dependent on both ion energy and average flux to the substrate. The ion energy can be accurately controlled by the amplitude of the positive voltage pulse while the average ion flux can be controlled by the duration of the negative pulse. Measurements of the plasma potential in front of the substrate and the ion saturation current at the substrate position allow explaining the mechanism of ion acceleration and the control of ion energy and flux. The effect of the pulsing configuration on the microstructure of the co-deposited films has been investigated by X-ray Diffractometry, Scanning Electron Microscopy and Atomic Force Microscopy, while the amount of noble gas enclosed in the coatings has been measured by Non-Rutherford Backscattering Spectrometry. Ne and Ar amount in the W co-deposited layers increases up to 3.0 at.% each as the amplitude of the positive pulse increases to + 300 V or the negative pulse duration decreases to 3 µs. The highest film crystallinity, with W(1 1 0) preferential growth, has been obtained for a positive pulse voltage of + 200 V and a negative pulse duration of 5 µs. The thickness of the deposited layers ranges between 350 nm in bipolar HiPIMS with a positive pulse voltage of + 300 V and 550 nm in monopolar HiPIMS.